HEAVY METAL EXPOSURE IN CHILDREN - Cabar, Huriye Demet; Oruc, Sena; Gümüş, Elif (Acta Scientiae et Intellectus, 2024)
Heavy metals have been ubiquitous in our lives in many ways and for different purposes for centuries. Heavy metals cause health effects not only in adults but also in children. Therefore, it is aimed to give information about the interaction of heavy metals to children and nursing approach in the study which is planned as a review by conducting literature search.